HUKUM EKONOMI SYARIAH TERHADAP PENGUASAAN HAK MILIK TANAH TANPA IZIN - Astuti, Linda Dwi; Rochmiatun, Siti (Program Studi Muamalah Fakultas Syariah dan Hukum, 2024)
Review of Sharia Economic Law on Control of Land Ownership Rights Without Permits in Tanjung Seteko Village, Indralaya District, Ogan Komering Ilir Regency. Land plays such an important role in every human life and business that it is possible for disputes to arise regarding land rights. Therefore, many people want to control or utilize land without the consent of the land owner. The problems in this research are: 1. What factors are behind the control of land ownership rights without permission in Tanjung Seteko Village, Indralaya District, Ogan Komering Ilir Regency? 2. What is the review of Sharia Economic Law regarding the control of land ownership rights without permission in Tanjung Seteko Village, Indralaya District, Ogan Komering Ilir Regency? This research uses field research methods. This research used a population of 94 people and a sample of 9 people. The data sources used are primary data and secondary data. Data collection techniques consist of interviews, observation and documentation. The data analysis technique uses descriptive qualitative. The results of this research show that 1. what factors are behind the control of property rights without permission in Tanjung Seteko Village, namely the low level of understanding of land control without permission, economic factors and negligence of land owners. 2. How does Sharia Economic Law review the control of land ownership rights without permission in Tanjung Seteko Village, which is haram and not permitted because it is an act of Ghasab. Because he has controlled someone else's land without any rights. In Sharia Economic Law, control of property rights without permission in Tanjung Seteko Village, namely does not fulfill the Principles of Justice and the Principles of Benefit. Actions carried out by land managers cause injustice to the land owner, and the land does not provide benefits in terms of the land owner or the surrounding community.